Illustrated Dictionary of Physics - Wertheim, Jame; Oxley,C; Wertheim, Jame; Oxley,C (Saffron Hills , London Usborne Publishing Ltd, 2006)
The Usborne Illustrated Dictionary of Physics, authored by Corinne Stockley, Chris Oxlade, and Jane Wertheim. This revised edition, published in 2006 by Usborne Publishing, serves as a comprehensive reference for students studying physics at Key Stage 3 and Key Stage 4 levels, aligning with SAT and GCSE curriculum. This dictionary is part of Usborne's Illustrated Dictionaries series, which aims to present scientific subjects in an engaging and student-friendly manner. It is partic Structured into six color-coded sections, the dictionary covers a broad range of physics topics, including radioactivity, heat, sound, and electricity. Each entry provides clear definitions of key terms and concepts, supplemented by detailed diagrams to aid understanding. The book also features comprehensive cross-referencing, facilitating connections between related topics. With 128 pages of content, it is designed to support students in grasping fundamental physics concepts through visual and accessible explanations. ularly beneficial for learners seeking a visual and structured approach to understanding physics